Plywood Gandang Tambua Tuning System - Puja Septiana; Wimbrayardi (Universitas Negeri Padang, 2024)
The process of making traditional musical instrument Gandang Tambua in Padang Pariaman Regency. This study aims to describe the process of making Gandang Tambua musical instruments. The approach used is a qualitative approach with descriptive research. This research was conducted with data collection techniques used were observation, interview and documentation techniques. The data analysis technique is done by reducing, presenting data and verifying this data aims to find out the structure, process, manufacturing techniques, playing techniques, of Gandang Tambua. This musical instrument is made of plywood and has holes (resonators), and uses goat skin. The results of this study indicate that the parts and stages of the process of making traditional musical instruments Gandang Tambua include: cutting plywood for the body of Gandang Tambua, processing goatskin (membrane), cleaning rattan, making iron battens, and how to produce sound, tuning system on traditional musical instruments Gandang Tambua. The tools used in the process of making traditional Gandang Tambua musical instruments include: Cater knife (plywood cutter), Cutting Saw, Hammer (Smoker), Measuring tool (meter), Pencil, Sandpaper, Screwdriver, Scissors, Bamboo type chamfer, Clamp. The materials are; Wooden battens (circle 40), plywood, goatskin, iron battens, rope, nails and, wood glue. The process of making Gandang Tambua musical instruments includes several stages, namely: 1) The process of making the body (plywood), until finishing fine and coarse sanding, 2) Leather processing, including shearing the skin using dry fuel ash and measuring the diameter width, 3) The installation process, including the skin to the Tambua drum body, install the iron batten and install the rope for tuning.